Cdt1 proteolysis is promoted by dual PIP degrons and is modulated by PCNA ubiquitylation. - Guarino, E; Shepherd, M; Salguero, I; Hua, H; Deegan, R; Kearsey, S (Oxford University Press, 2011)
Cdt1 plays a critical role in DNA replication regulation by controlling licensing. In Metazoa, Cdt1 is regulated by CRL4(Cdt2)-mediated ubiquitylation, which is triggered by DNA binding of proliferating cell nuclear antigen (PCNA). We show here that fission yeast Cdt1 interacts with PCNA in vivo and that DNA loading of PCNA is needed for Cdt1 proteolysis after DNA damage and in S phase. Activation of this pathway by ultraviolet (UV)-induced DNA damage requires upstream involvement of nucleotide excision repair or UVDE repair enzymes. Unexpectedly, two non-canonical PCNA-interacting peptide (PIP) motifs, which both have basic residues downstream, function redundantly in Cdt1 proteolysis. Finally, we show that poly-ubiquitylation of PCNA, which occurs after DNA damage, reduces Cdt1 proteolysis. This provides a mechanism for fine-tuning the activity of the CRL4(Cdt2) pathway towards Cdt1, allowing Cdt1 proteolysis to be more efficient in S phase than after DNA damage.